Characterization of Flavin-Based Fluorescent Proteins: An Emerging Class of Fluorescent Reporters - Mukherjee, Arnab (Public Library of Science, 2013)
Fluorescent reporter proteins based on flavin-binding photosensors were recently developed as a new class of genetically encoded probes characterized by small size and oxygen-independent maturation of fluorescence. Flavin-based fluorescent proteins (FbFPs) address two major limitations associated with existing fluorescent reporters derived from the green fluorescent protein (GFP)–namely, the overall large size and oxygen-dependent maturation of fluorescence of GFP. However, FbFPs are at a nascent stage of development and have been utilized in only a handful of biological studies. Importantly, a full understanding of the performance and properties of FbFPs as a practical set of biological probes is lacking. In this work, we extensively characterize three FbFPs isolated from Pseudomonas putida, Bacillus subtilis, and Arabidopsis thaliana, using in vitro studies to assess probe brightness, oligomeric state, maturation time, fraction of fluorescent holoprotein, pH tolerance, redox sensitivity, and thermal stability. Furthermore, we validate FbFPs as stable molecular tags using in vivo studies by constructing a series of FbFP-based transcriptional constructs to probe promoter activity in Escherichia coli. Overall, FbFPs show key advantages as broad-spectrum biological reporters including robust pH tolerance (4–11), thermal stability (up to 60°C), and rapid maturation of fluorescence (<3 min.). In addition, the FbFP derived from Arabidopsis thaliana (iLOV) emerged as a stable and nonperturbative reporter of promoter activity in Escherichia coli. Our results demonstrate that FbFP-based reporters have the potential to address key limitations associated with the use of GFP, such as pH-sensitive fluorescence and slow kinetics of fluorescence maturation (10–40 minutes for half maximal fluorescence recovery). From this view, FbFPs represent a useful new addition to the fluorescent reporter protein palette, and our results constitute an important framework to enable researchers to implement and further engineer improved FbFP-based reporters with enhanced brightness and tighter flavin binding, which will maximize their potential benefits.